2019
DOI: 10.1080/15287394.2019.1648346
|View full text |Cite
|
Sign up to set email alerts
|

Effects of astaxanthin and canthaxanthin on oxidative stress biomarkers in rainbow trout

Abstract: Farmed trout are commonly fed carotenoid-enriched diets during the finishing period to acquire the typical red-to-pink flesh color in salmonid muscle. The aim of this study was to examine the effects of the two xanthophylls, astaxanthin (Ax) or canthaxanthin (Cx), administered individually or in combination, on oxidative stress biomarkers in kidney and liver of rainbow trout. Specimens were fed Ax and/or Cx enriched diets with 75 or 25 mg of each compound/kg for eight weeks. Changes in concentration of oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…Concerning the effect of dietary AX supplementation on endogenous antioxidant enzymes (both in terms of activities and mRNA level of GR), the enzyme involved in the reduction of GSSG to GSH using NADPH as a reducing cofactor [60] was increased, whereas other antioxidant enzymes were not significantly affected. Similar to our results, an enhanced GR activity was reported in liver of rainbow trout after 8 weeks of AX supplementation [12].…”
Section: Control Of Antioxidant Enzymes By Episodic Hyperoxia and Diesupporting
confidence: 92%
See 2 more Smart Citations
“…Concerning the effect of dietary AX supplementation on endogenous antioxidant enzymes (both in terms of activities and mRNA level of GR), the enzyme involved in the reduction of GSSG to GSH using NADPH as a reducing cofactor [60] was increased, whereas other antioxidant enzymes were not significantly affected. Similar to our results, an enhanced GR activity was reported in liver of rainbow trout after 8 weeks of AX supplementation [12].…”
Section: Control Of Antioxidant Enzymes By Episodic Hyperoxia and Diesupporting
confidence: 92%
“…The significant increase of GSH/GSSG could be related to the fact that glutathione is recycled in a NADPH-dependent reaction by GR, and the GR activity was significantly increased in fish fed the ASTA diet. Similarly, in a study with rainbow trout fed an AX-supplemented diet for 8 weeks, elevated liver GR activity allowed liver GSH amounts to be sustained [12]. In addition, NADPH synthesis seems to be augmented by the ASTA diet through the increase in g6pd mRNA level.…”
Section: Control Of Glutathione Metabolism By Episodic Hyperoxia and mentioning
confidence: 92%
See 1 more Smart Citation
“…In aquatic species, the levels of those biomolecules involved in antioxidant and detoxifying defence can be used as informative biomarkers to investigate the oxidative stress exerted by xenobiotics (Al Kaddissi et al 2012Kaddissi et al , 2014Cozzari et al 2015;Elia et al 2007Elia et al , 2017Elia et al , 2018Elia et al , 2019Elia et al , 2020Magara et al 2018Magara et al , 2019. Metallothioneins (MTs) are proteins able to bind heavy metals, acting as homeostatic buffers.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that canthaxanthin is capable of scavenging reactive oxygen species and quenching singlet oxygen [ 9 , 27 ]. In addition, in vivo experiments revealed that canthaxanthin supplementation led to a decrease in lipid peroxidation to prevent induced liver DNA damage in rats [ 28 ] and to enhance the antioxidant defense in rat liver [ 29 , 30 ]. At the immunomodulatory level, an interesting example was observed in a mouse cell line, in which canthaxanthin increased the activity of alkaline phosphatase, an enzyme found in several tissues involved in the detoxification of lipopolysaccharides.…”
Section: Introduction: Characterization and Biosynthesis Of Canthamentioning
confidence: 99%